Frailty, Psychoactive Medications, and Cognitive Dysfunction Are Associated With Poor Patient‐Reported Outcomes in Cirrhosis. Issue 4 (19th February 2019) - Tapper, Elliot B.; Baki, Jad; Parikh, Neehar D.; Lok, Anna S.
Abstract : Cirrhosis is associated with disabling symptoms and diminished health‐related quality of life (HRQOL). However, for patients with compensated disease, data are limited regarding associations with poor patient‐reported outcomes (PROs). We prospectively enrolled 300 patients with cirrhosis and portal hypertension without a history of hepatic encephalopathy (HE) and reviewed medical and pharmacy records. We characterized determinants of PROs using the 8‐item Short‐Form Health Survey (SF‐8) scale (0‐100) and sleep quality using the Pittsburgh Sleep Quality Index (PSQI; poor sleep >5). Disability and frailty measures were assessed using activities of daily living (ADLs), falls, hand‐grip, and chair‐stands. Cognitive function was measured using weighted‐lures from the Inhibitory Control Test (ICT). The median age of our cohort was 60 (interquartile range [IQR], 52‐66) years, 56.3% were male, and 70% Child class A. All patients had portal hypertension, 76% had varices, and 41% had a history of ascites (predominantly well controlled). The median Model for End‐Stage Liver Disease with Sodium (MELD‐Na) score was 9 (IQR, 7‐13). The overall median SF‐8 was 70 (IQR, 54‐86). Multivariate analysis showed that after adjusting for age, sex, education, and MELD‐Na, performance on chair‐stands (9.28 HRQOL points [95% confidence interval CI, 4.76‐13.8] per 10‐stands), ADL dependence (–6.06 [–10.8 to –1.36]), opiate use (–5.01 [–7.84 to –2.19]), benzodiazepine use (–3.50 [–6.58 to –0.42]), and ICT performance (–0.10 [–0.20 to 0.001] per weighted‐lure) were significantly associated with HRQOL. Among patients completing the ICT, poor HRQOL (score <50) was significantly associated with chair‐stands (odds ratio [OR] per 10‐stands, 0.24; 95% CI [0.11‐0.56]) and weighted lures (OR per weighted‐lure, 1.01 [1.00‐1.03]). Poor sleep quality was associated with opiate use (OR, 2.85 [1.11‐7.29]) and lures (OR per‐lure, 1.03 [1.00‐1.05]). Conclusion: Disability, chair‐stand performance, cognitive dysfunction, as well as psychoactive medication use are significantly associated with PROs in patients with clinically stable cirrhosis.